O plano de gerenciamento dos resíduos dos serviços de saúde na atenção básica e ambulatório de especialidades do Sistema Único de Saúde no município de São Roque - Camargo, Ândrea Regina de (Universidade Federal de São Carlos, 2016)
Não disponível
Management plan waste health services in primary care and clinic of the single system specialties health in San Roque Municipality
Keywords: Sistema Único de Saúde (Brasil); Resíduos de serviços de saúde; Medical wastes; Health care; Waste management; Health professional; Sustainability; OUTROS